29. Golden Grove Discovery Case Histories ? Introduction (Society for Mining, Metallurgy & Exploration, 1991)
The Golden Grove Project area is located 220 km (137 miles) east of Geraldton in Western Australia (Fig. 1). The project is a joint venture involving Amax Exploration (Australia) Inc. (Amax), Electrolytic Zinc Co. of Australasia Ltd. (EZ), and Esso Exploration & Production Australia Inc. (Esso), each with 31 116% interest, and Aztec Exploration Pty., Ltd. (Aztec), with a 3 1/2% carried and a 3% contributing interest. The venture covers two significant volcanogenic massive sulfide deposits and some 40 km (25 miles) of highly prospective Archean volcanics. During the course of the past 12 years (to 1983), all four companies were responsible for operating the project at one time or another and all influenced the discoveries. The Gossan Hill and Scuddles deposits are typical examples of volcanogenic massive sulfide deposits associated with Archean explosive submarine acid to intermediate volcanic complexes. They are located in the northwesterly trending Yalgoo greenstone belt of the West Australian Archean Shield. Gossan Hill, located in 1972, is essentially a copper deposit with minor zinc lenses; to date, 97 diamond holes have delineated a geological resource* estimated to contain 13 Mt (14.3 million st) of of 3.4% Cu and 13 g/t (0.38 oz per ton) Ag in the main lenses with minor lenses totaling 2 Mt (2.2 million st) of 3.7% Cu and 17 g/t (0.49 oz per ton) Ag and 1.7 Mt (1.9 million st) grading 1.5% Pb, 14% Zn, and 87 g/t (2.8 oz per ton) Ag. Scuddles is a zinc-copper deposit with gold and silver credits. It *Resource estimate provided by Esso for inclusion in Aztec Exploration Pty. Ltd. 1982 Annual Report was discovered in 1979 and, to the end of 198 1, had been delineated with 42 diamond holes. On the basis of this drilling, a geological resource* of 26 Mt (28.7 million st) has been estimated in three coalescing lenses. The lenses comprise 7.5 Mt (8.3 million st) of 2.1 % Cu, 12 g/t (0.35 oz per ton) Ag, and 0.3 g/t (0.009 oz per ton) Au; 7.6 Mt (8.4 million st) of 0.4% Cu, 9.9% Zn, 73 g/t (2.3 oz per ton) Ag, and 0.7 g/t (0.02 oz per ton) Au; and 1 1.0 Mt (1 2.1 mil lion st) of 1.1 % Cu, 9.3% Zn, 8 1 g/t (2.6 oz per ton) Ag, and 1.5 g/t (0.044 oz per ton) Au. Readers are referred to Frater (1978) and Harris et a). (1982) for a more detailed geological account of these deposits.